2003
DOI: 10.1002/ijc.11687
|View full text |Cite
|
Sign up to set email alerts
|

DNA bulky adducts in a Mediterranean population correlate with environmental ozone concentration, an indicator of photochemical smog

Abstract: 1 Ozone (O 3 ), the major oxidant component in photochemical smog, mostly derives from photolysis of nitrogen dioxide. O 3 may have biologic effects directly and/or via free radicals reacting with other primary pollutants and has been reported to influence daily mortality and to increase lung cancer risk. Although DNA damage may be caused by ozone itself, only other photochemical reaction products (as oxidised polycyclic aromatic hydrocarbons) may form bulky DNA adducts, a reliable biomarker of genotoxic damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…This is consistent with a previous investigation showing a relationship between cumulative O 3 exposure and DNA adduct formation among nonsmokers in Florence, Italy (34). O 3 is a marker of photochemical smog, being produced by a complex series of reactions involving hydrocarbons and nitrogen dioxide, emitted primarily during combustion of fossil fuels by industry and transportation activities, and driven by UV radiation in sunlight (3).…”
Section: Dna Adducts and Lung Cancer Risksupporting
confidence: 92%
“…This is consistent with a previous investigation showing a relationship between cumulative O 3 exposure and DNA adduct formation among nonsmokers in Florence, Italy (34). O 3 is a marker of photochemical smog, being produced by a complex series of reactions involving hydrocarbons and nitrogen dioxide, emitted primarily during combustion of fossil fuels by industry and transportation activities, and driven by UV radiation in sunlight (3).…”
Section: Dna Adducts and Lung Cancer Risksupporting
confidence: 92%
“…12 Therefore, it is not necessarily relevant, at least in causal assessment, to distinguish among single pollutants; rather, they might interact in unpredictable ways. O 3 has been found to damage DNA in 2 epidemiological studies, including the present one, 13,14 but its role is more difficult to assess because of strong negative association with other 2 , 27 vs <27 lg/m 3 for PM10, and 11 vs <11 lg/m 3 for SO 2 (see text).-2 As in footnote 1 but additionally adjusted by BMI, education, intake of fruit and vegetables, intake of meat, intake of alcohol, physical activity.-3 As in footnote 1 but additionally adjusted by cotinine.- 4 As in footnote 1 but additionally adjusted by occupational index (see text).…”
Section: Discussionsupporting
confidence: 50%
“…In a previous study carried out in the frame of EPIC-Florence study, by using the same method of DNA adducts detection ( 32 P-postlabelling), we reported a significant correlation between individual levels of bulky DNA adducts and the mean environmental levels of a specific air pollutant (ozone), measured in a period prior the blood drawing, in never-smokers residing in the Florence urban area and not occupationally exposed to vehicle traffic pollution [36]. The association between bulky DNA adducts and ozone concentration has been confirmed in a larger nested case-control study carried out in the frame of a larger European prospective study [25].…”
Section: Discussionmentioning
confidence: 85%